2015
DOI: 10.1590/s1679-45082015ao3331
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects of influenza A(H1N1)pdm09 cases reported during the pandemic in Brazil, 2009-2010

Abstract: Objective:To describe the clinical aspects of cases of influenza A(H1N1)pdm09 in Brazil.Methods:A descriptive study of cases reported in Sistema de Informação de Agravos de Notificação (SINAN), 2009-2010.Results:As the final classification, we obtained 53,797 (56.79%) reported cases confirmed as a new influenza virus subtype, and 40,926 (43.21%) cases discarded. Fever was the most common sign, recorded in 99.74% of the confirmed and 98.92% of the discarded cases. Among the confirmed cases, the presence of como… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
1
3
0
2
Order By: Relevance
“…Other common symptoms such as dyspnea and respiratory discomfort were present in 76.7% and 61.8%, respectively, in those who presented the negative outcome (death). These symptoms appear as the main and most frequently presented, according to the results of this study, corroborating the findings of previous studies [20] , [21] . On the other hand, Mazon et al reported that cough was not a main symptom [22] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Other common symptoms such as dyspnea and respiratory discomfort were present in 76.7% and 61.8%, respectively, in those who presented the negative outcome (death). These symptoms appear as the main and most frequently presented, according to the results of this study, corroborating the findings of previous studies [20] , [21] . On the other hand, Mazon et al reported that cough was not a main symptom [22] .…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the influenza A subtype most found in the patients of this study was H3N2, of which 53.9% died, as in the study by Fielding et al, which reported most cases of H3N2 subtype influenza [25] . On the other hand, the results of Araújo et al, Rossetto and Luna, and Silveira et al [20] , [21] , [23] showed that the predominant subtype of influenza A was H1N1, as well as the Australian study, which analyzed influenza outbreaks, showing that H1N1 was predominant [26] . The study by Muscatello et al also found the most recorded influenza A in the studied period with a rate of 70%, but did not analysis the specific subtype [24] .…”
Section: Discussionmentioning
confidence: 99%
“…The H1N1-positive subgroup presented a higher frequency of fever, cough and tachypnea and lower leukocyte count when compared to the H1N1-negative subgroup. Cough is a characteristic of H1N1 infection, [21][22][23] as well as leukopenia. 9 In Taiwan, leukopenia was found in 64.2% of cases and was more frequent in H1N1positive.…”
Section: Discussionmentioning
confidence: 99%
“…No Brasil, houve em torno de 40.000 casos de síndrome respiratória aguda grave (SRAG) e, aproximadamente, 1.700 mortes no período de oito meses, desde a Declaração de Emergência de Saúde Pública de Importância Internacional (ESPII) pela OMS em abril de 2009 11 . A gravidade da pandemia, ainda que com recursos médicos e científicos superiores aos cenários anteriores, revelou a necessidade e a urgência de uma nova abordagem de vigilância epidemiológica, e, como requisito básico, uma maior eficiência na detecção e monitoramento de novos casos 12 .…”
Section: Introductionunclassified